2023
DOI: 10.1002/ejsp.2969
|View full text |Cite
|
Sign up to set email alerts
|

When one's partner wants out: Awareness, attachment anxiety and accuracy

Abstract: Can a person tell whether their romantic partner wants to break up and, if so, how is such accuracy associated with their own attachment anxiety? We examined these questions by proposing and assessing the construct of perceived partner dissolution consideration (PPDC), including its validity. We then assessed the extent to which partners were accurate in their perceptions of each other's dissolution consideration, focusing on the perceiver's attachment anxiety as a potential moderator. Specifically, in two stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…In such cases, when someone sees strong potential for the new relationship to become committed, they may prefer their partner to be more committed than they currently are. Conversely, when someone does not see as much potential for the future, perceiving that their partner wants to leave (Tan et al, 2023) -or they realize their own commitment is beginning to wane -a reciprocal developmental trajectory may commence, in which they realize that they would like to leave the relationship and they may prefer their partner also become less committed (VanderDrift et al, 2009). In both examples, people's preference is for their partner's commitment to match their own commitment level (or desired commitment level; see Pusch et al, 2023, for research on the benefits of minimizing discrepancies in self-reported closeness between partners within a relationship).…”
Section: Perceiving and Influencing A Partner's Commitment Levelmentioning
confidence: 99%
“…In such cases, when someone sees strong potential for the new relationship to become committed, they may prefer their partner to be more committed than they currently are. Conversely, when someone does not see as much potential for the future, perceiving that their partner wants to leave (Tan et al, 2023) -or they realize their own commitment is beginning to wane -a reciprocal developmental trajectory may commence, in which they realize that they would like to leave the relationship and they may prefer their partner also become less committed (VanderDrift et al, 2009). In both examples, people's preference is for their partner's commitment to match their own commitment level (or desired commitment level; see Pusch et al, 2023, for research on the benefits of minimizing discrepancies in self-reported closeness between partners within a relationship).…”
Section: Perceiving and Influencing A Partner's Commitment Levelmentioning
confidence: 99%